The effects of subjective loss of control on risk-taking behavior: the mediating role of anger - Beisswingert, Birgit M.; Zhang, Keshun; Goetz, Thomas; Fang, Ping; Fischbacher, Urs (Frontiers in Psychology, 2015)
Based on the Appraisal Tendency Framework on the antecedents and consequences of emotions two experimental studies examined the relationship between externally caused loss of control experiences and risk-taking behavior, as well as the assumed mediation of this relationship by the emotion anger. An experimental paradigm for inducing externally caused and consequently externally attributed loss of control which should lead to experiences of anger was developed and pretested in a Pilot Study. The relationship between loss of control experiences, anger and risk-taking behavior was investigated using two separate student samples from Germany (N = 84, 54% female) and China (N = 125; 64% female). In line with our hypotheses, results showed that anger mediated the link between subjective loss of control experiences and increasing risk-taking behavior. Multiple group comparisons revealing similar patterns in both samples affirmed the results’ cross-cultural generalizability. These results implicate that anger makes people less risk averse in the process of economic decision making.